Knowledge and its creation – the case of introducing product to the market - Soviar, Jakub; Závodská, Anna (Business: Theory and Practice, 2011)
This paper deals with a marketing strategy of product Pregnium® of Walmark Company from the view of knowledge creation and knowledge sharing for successful introducing of product to the market. Product is a nutritional supplement which is intended for pregnant women. This paper is divided into the following main chapters: First chapter deals with knowledge management of main relevant definitions and resources. Second chapter deals with characteristics of market and product. Third chapter shows a research method and main results. Fourth chapter, the discussion, shows the main points of created marketing strategy. The last chapter is intended as a conclusion in terms of knowledge use by creating the given marketing strategy.